2014
DOI: 10.5130/ccs.v6i1.3737
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and limitations of using cricket as a sport for development tool in Samoa

Abstract: This study investigates opportunities and challenges associated with the use of sport -in this case cricket -as a community development tool in Samoa. This Pacific Island nation, like others in the region, has been the focus of various development programs in the post-colonial era, with developed economy neighbours like Australia and New Zealand providing aid funding. Some of these programs have involved sport as a development tool, underpinned either by funding from the national government, foreign aid agenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In line with previous work in the SFD sector (see e.g., Khoo et al, 2014;Sugden, 2010), their research underscored the importance SPORT-FOR-DEVELOPMENT IN THE SOUTH PACIFIC 10 of understanding and considering local context within a SFD program. Here, this related to putting relevant strategic parameters in place that would help facilitate future benefits, including macro-level education impacts.…”
Section: Sport-for-development In the South Pacificsupporting
confidence: 64%
See 1 more Smart Citation
“…In line with previous work in the SFD sector (see e.g., Khoo et al, 2014;Sugden, 2010), their research underscored the importance SPORT-FOR-DEVELOPMENT IN THE SOUTH PACIFIC 10 of understanding and considering local context within a SFD program. Here, this related to putting relevant strategic parameters in place that would help facilitate future benefits, including macro-level education impacts.…”
Section: Sport-for-development In the South Pacificsupporting
confidence: 64%
“…Schulenkorf et al's (2016) review of SFD research demonstrated that over half of all published SFD research studies examined the actual outcomes of specific programs and interventions. As interventions are often supported by government and sponsor funding, this focus is hardly surprising; in fact, pressures to explain and justify external spending against desired outcomes have led to an increased emphasis on monitoring and evaluating sport-based development initiatives (Schulenkorf & Adair, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• International sporting bodies such as the IOC and FIFA have often made strong policy statements in support of the role of sport in development and have funded a variety of organisations to implement programmes in particular regions, countries and contexts (Giulianotti, 2011a;Manzo, 2012). There are also examples of national governing bodies and other sport organisations that have engaged with development issues relevant to their own country contexts (Banda, 2017;Khoo et al, 2014).…”
Section: Non-state Actorsmentioning
confidence: 99%
“…This outcome speaks to the difficulty in achieving buy in from all (potential) event stakeholders, and also reinforces Misener's (2015) argument for the importance of the policy environment and how this can enable or constrain the leveraging of an event. Moreover, in the case of externally funded development projects, local power dynamics and the pressure to deliver development outcomes present significant factors that impact the willingness to cooperate, and often, organizations will only contribute if they can claim and sell project outcomes as their own exclusive achievements (see Khoo et al, 2014;Schulenkorf & Edwards, 2012). For the FSJP Festival, it meant that significant opportunities to maximize educational and health-related outcomes remained unused.…”
Section: Educationalmentioning
confidence: 99%
“…The sporting festival had a predominant focus on football (or soccer) games and interschool competitions, but also included other sporting activities including rugby, netball, and kirikiti-the local and traditional version of cricket played in Sāmoa (for more information on the game and its origins, see Khoo, Schulenkorf, & Adair, 2014). In addition to sport, the festival also offered cultural activities, educational workshops, and healthrelated awareness sessions that were co-organized by local stakeholders, including the Sāmoan Ministry of Health, the Red Cross, the Sāmoan Victims Support Group, local educators and social workers, as well as community members including elders and volunteers.…”
Section: Schulenkorf and Schlenkermentioning
confidence: 99%